Genotype and clinical care correlations in craniosynostosis: Findings from a cohort of 630 Australian and New Zealand patients. Issue 4 (11th October 2013) - Roscioli, T.; Elakis, G.; Cox, T.C.; Moon, D.J.; Venselaar, H.; Turner, A.M.; Le, T.; Hackett, E.; Haan, E.; Colley, A.; Mowat, D.; Worgan, L.; et al.
Abstract Craniosynostosis is one of the most common craniofacial disorders encountered in clinical genetics practice, with an overall incidence of 1 in 2, 500. Between 30% and 70% of syndromic craniosynostoses are caused by mutations in hotspots in the fibroblast growth factor receptor (FGFR) genes or in the TWIST1 gene with the difference in detection rates likely to be related to different study populations within craniofacial centers. Here we present results from molecular testing of an Australia and New Zealand cohort of 630 individuals with a diagnosis of craniosynostosis. Data were obtained by Sanger sequencing of FGFR1, FGFR2, and FGFR3 hotspot exons and the TWIST1 gene, as well as copy number detection of TWIST1. Of the 630 probands, there were 231 who had one of 80 distinct mutations (36%). Among the 80 mutations, 17 novel sequence variants were detected in three of the four genes screened. In addition to the proband cohort there were 96 individuals who underwent predictive or prenatal testing as part of family studies. Dysmorphic features consistent with the known FGFR1‐3/TWIST1‐associated syndromes were predictive for mutation detection. We also show a statistically significant association between splice site mutations in FGFR2 and a clinical diagnosis of Pfeiffer syndrome, more severe clinical phenotypes associated with FGFR2 exon 10 versus exon 8 mutations, and more frequent surgical procedures in the presence of a pathogenic mutation. Targeting gene hot spot areas for mutation analysis is a useful strategy to maximize the success of molecular diagnosis for individuals with craniosynostosis. © 2013 Wiley Periodicals, Inc.